Prototipe Sistem Deteksi Jantung Manusia dan Lokasi Berbasis Internet of Things (IoT) - Almira Budiyanto; Ardymas Jati Putu Mardana (Aviation Electronics, Information Technology, Telecommunications, Electricals, Controls (AVITEC), 2021)
The deaths caused by heart and blood vessel diseases reached 17.7 million people or 32.26 percent of total deaths in the world. The representation of heart health can be seen from the number of heart rate (HR) and oxygen saturation (SpO2). The purpose of this study is to determine the condition of the human body through the number of heartbeats and SpO2 using the MAX30100 sensor and to be able to find out the location of the patient via GPS Adafruit Ultimate Breakout. GPS calibration uses two calculation methods, namely using the Haversine formula and using the distance measurement feature on Google Earth. The method is then compared to get the difference between the coordinates obtained by the smartphone GPS as a reference with the patient's GPS. The HR measurement calibration on the MAX30100 sensor is then compared with the pulse on the wrist for accuracy.. The results of this study indicate the level of coordinate accuracy obtained by GPS Adafruit is not more than 5 meters. The average HR accuracy value is 98,23 percent and the SpO2 calibration results get an accuracy of 98,99 percent. The waiting time required for the GPS to receive coordinates from the satellite with the GPS condition uncovered by the casing is about 7 to 13 minutes, while when the casing is closed the GPS cannot get the coordinates. MAX30100 can work optimally and obtain accurate values when the patient is in a relaxed position and does not do too much movement.